Applications of Domino Transformations in Organic Synthesis. Volumes 1 and 2. Science of Synthesis Workbench Edition. Edited by Scott A. Snyder. Issue 42 (6th October 2016) - Menche, Dirk
Abstract : Thieme, Stuttgart 2016. 1260 pp., softcover, € 449.00.—ISBN 978‐3132401631